Endoscopic treatment of esophageal and colo-rectal fistulas with fibrin glue - Del Rio, P.; Dell'Abate, P.; Soliani, et al., P. (Acta Biomedica Atenei Parmensis, 2005)
So far, the use of fibrin glue has been limited to the treatment of anal, recto-vaginal and enterocutaneous fistulae. Between 1991 and 2003 we performed the treatment of anastomotic leaks of the upper and lower gastro-intestinal tract with fibrin glue in 13 selected patients. In our experience the treatment with fibrin glue has been proved to be effective in the selected cases. If the fistulae clinically occured 7 days after surgery a higher number of endoscopic sessions were necessary than in patients with earlier appearance of anastomotic leakage.The utilization of fibrin glue for the endoscopic management of anastomotic leakages after surgery can be successful and safe if applied in selected patients.